Practice-led: design factor analysis in developing new Mountain Bike (MTB) pedal - Dolah, Mohd Shahrizal; Amran, Mohamad Amaluddin; Yusof, Aminuddin; Shahbudin, Shahrul Azman; Raja Ahmad Effendi, Raja Ahmad Azmeer; Ramly, Saiful Hasley (Universiti Putra Malaysia Press, 2022)
This paper has investigated a practice-led design method for product designers in designing a new mountain bike (MTB) pedal. According to the World Bank, it is estimated, there are already more than two billion bikes in use around the world in 2017 and the number increasing every year. The main objective of the study is to understand the cause of an accident and to provide design factors for a designer in developing a new MTB pedal. Fieldwork done in Malaysia from 2018 to 2020 revealed that, 85.2% of mountain bike riders involved in an accident (physical injuries) during bike event that course by the mishandling of bike pedal. Direct observation and action design research was adopted as the main research method where the author involved actively participating in MTB event to gain the main data. Product design specifications were listed that could help in reducing physical injuries among mountain bike riders (MBR). Eight design factors were listed as the main design priority in the product design specification. The product design specifications (PDS) were used as design guidance for designer in developing a new MTB pedal that could meet the requirement and the preferences of the mountain bike riders.